Human Endometrial Fibroblasts Derived from Mesenchymal Progenitors Inherit Progesterone Resistance and Acquire an Inflammatory Phenotype in the Endometrial Niche in Endometriosis - Barragan, Fatima (Biol Reprod, 2016)
Human endometrium undergoes cyclic regeneration involving stem/progenitor cells, but the role of resident endometrial mesenchymal stem cells (eMSC) as progenitors of endometrial stromal fibroblasts (eSF) has not been definitively demonstrated. In endometriosis, eSF display progesterone (P(4)) resistance with impaired decidualization in vivo and in vitro. To investigate eMSC as precursors of eSF and whether endometriosis P(4) resistance is inherited from eMSC, we analyzed transcriptomes of eutopic endometrium eMSC and eSF isolated by fluorescence-activated cell sorting (FACS) from endometriosis (eMSC(endo), eSF(endo)) and controls (eMSC(control), eSF(control)) and their derived primary cultures. Differentially expressed lineage-associated genes (LG) of FACS-isolated eMSC and eSF were largely conserved in endometriosis. In culture, eSF(control) maintained in vitro expression of a subset of eSF LG and decidualized in vitro with P(4). The eMSC(control) cultures differentiated in vitro to eSF lineage, down-regulating eMSC LG and up-regulating eSF LG, showing minimal transcriptome differences versus eSF(control) cultures and decidualizing in vitro. Cultured eSF(endo) displayed less in vitro LG stability and did not decidualize in vitro. In vitro, eMSC(endo) differentiated to eSF lineage but showed more differentially expressed genes versus eSF(endo) cultures, and did not decidualize in vitro, demonstrating P(4) resistance inherited from eMSC(endo). Compared to controls, cultures from tissue-derived eSF(endo) uniquely had a pro-inflammatory phenotype not present in eMSC(endo) differentiated to eSF in vitro, suggesting divergent niche effects for in vivo versus in vitro lineage differentiation. These findings substantiate eMSC as progenitors of eSF and reveal eSF in endometriosis as having P(4) resistance inherited from eMSC and a pro-inflammatory phenotype acquired within the endometrial niche.